Back Cover: Water‐Mediated Synthesis of a Superionic Halide Solid Electrolyte (Angew. Chem. Int. Ed. 46/2019). Issue 46 (24th October 2019) - Li, Xiaona; Liang, Jianwen; Chen, Ning; Luo, Jing; Adair, Keegan R.; Wang, Changhong; Banis, Mohammad Norouzi; Sham, Tsun‐Kong; Zhang, Li; Zhao, Shangqian; Lu, Shigang; Huang, Huan; et al.
Abstract : A facile and scalable method for the synthesis of a Li3 InCl6 superionic conductor based on a water‐mediated route is described by X. Sun et al. in their Communication on page 16427 ff. Reversible conversion between Li3 InCl6 and Li3 InCl6  ⋅ 2 H2 O has been confirmed, thus ensuring high stability toward air and humidity, as well as recoverable high ionic conductivity.